Modifying gas transfer membranes with nanoscale zero-valent iron: effects on membrane material properties, treatment performance, and biofilm thickness - Hanay, Ozge; Aksoy, Yunus; Celik, Aytekin; Yegin, Mustafa (Iwa Publishing, 2024)
Excessive membrane biofilm growth on membrane fibers depends on various factors, with membrane properties playing a pivotal role in influ- encing microbial affinit y for the membrane. To investigate the antibacterial impact of nano-sized zero-valent iron (nZVI) on membrane biofilm structure, pristine (polyvinylidene fluoride (PVDF)) only: HF-0 (PVDF:20/nZVI:0 w/w) and four gas transfer membranes (PVDF:nZVI at different concentrations: HF-1 (PVDF:20/nZVI:0.25 w/w), HF-2 (PVDF:20/nZVI:0.50 w/w), HF-3 (PVDF:20/nZVI:0.75 w/w), HF-4 (PVDF:20/nZVI:1.0 w/w) ) were produced. These membranes were assessed for surface morphology, porosity, gas permeability, and biofilm thickness, which ultimately affect biochemical reaction rate s in membrane biofilm reactors (MBfRs). Various MBfRs utilizing these gas transfer membranes were operated at different hydraulic retention times (HRTs) and oxygen pressures to assess chemical oxygen demand (COD) removal efficiency and nitrification performance. Incorporating nZVI into the PVDF polymer solution increased surface hydrophilicit y and porosit y but reduced Young's Modulus and oxygen diffusion coefficients. Confocal laser scanning microscopy (CLSM) analysis revealed an average biofilm thickness of 700 ,im in HF-0, HF1, and HF-3, with a 100 ,im decrease in HF-2, even though Escherichi a coli growth was observed in HF-3 fibers. Regardless of nZVI dosage, a significant decline in COD removal and nitrification rate s occurred at low HRT s and gas pressures.
Keywords: ammonium removal; biofilm thickness; membrane biofilm reactor; zero-valent iron